(untitled) (Tri-Chandra Journal of Anthropology, 2025)
In the literature on household-gendered work, women are conceptualized as ’producers’ while men are conceptualized as ’consumers’ of women’s services. Rather than contesting this argument, this paper shows that food may be used for an unlimited of purposes, whether to resist, exercise, change, express, or even reinforce the sexual division of labor. Specifically, conversations with 20 middle-class Brahman women residing in Kathmandu Valley show that they derive personal gains from food preparation as it facilitates the construction of gender and class identities. Although, women’s attitudes and practices generally reproduce the dominant gender ideology they do not perceive food making as a form of gender subjugation since this role is colored by how the ’self’ is constructed. Furthermore, women view this role to be a significant cultural value, which may be continuously adapted, reproduced, modified, revived, recreated, and elaborated in whichever, they feel happy and benefit from the situation.